Role of ayurveda detoxification and dietary modification on restoration of euglycemia in T2DM patients - Imran, Sumera; Sabir, Imran; Mandole, Rahul; Khan, Sadik (International Journal of Research in Medical Sciences, 2023)
Background: The current study sought to assess restoration of carbohydrate metabolism in known type 2 diabetes patients to achieve good glycemic control without dependency on oral antihyperglycemic agents by implementing the comprehensive diabetes control (CDC) program. Methods: A retrospective, single-centre observational study was conducted from April 2021 to April 2022. Patients who were known cases of type 2 diabetes mellitus aged 18 years and above who underwent at least 6 sessions of the CDC program were included in this study. Patients with type 1 diabetes mellitus were excluded from the study. Follow-up was conducted after 90 days. Baseline data was compared with follow-up data. Results: A total of 69 patients were assessed in this study. Of the patients, testing was performed on 95.8% patients, of which. 92.8% patients were found to have negative glucose tolerance and 7.3% were found to have impaired glucose tolerance. Conclusions: The CDC program can be useful to restore euglycemia in know type 2 diabetic patients by reducing insulin resistance caused by central obesity.